The Role of the Serang City Regional Government in Developing Culinary Tourism Potential to Increase Original Regional Income Based on Serang City Regional Regulation Number 11 of 2019 concerning the Implementation of Tourism Businesses - Noviyanti, Indri (Universitas Sultan Ageng Tirtayasa, 2023)
The tourism industry has proven its role as an alternative economic activity that can improve community welfare and contribute to regional income. Identify the problem, how is the role of the Serang City regional government implemented in developing the potential of culinary tourism as an increase in local revenue? and What are the obstacles and solutions for the regional government of Serang City in developing the potential of culinary tourism as an increase in local revenue? The theories used are authority theory and tourism management theory. The method used is empirical juridical with data analysis through a qualitative approach using primary data in the form of interviews and secondary data. The results of the research show that the implementation of the role of regional government has not been fully implemented. The construction and development plans for the culinary specialty area have not yet been fully realized, because the management is still in the process of structuring and adjusting. Regional government support in dealing with obstacles and solutions for developing culinary tourism potential is not yet optimal, because the budget is not focused on culinary center development activities. In conclusion, the government's efforts in managing tourism are carried out by carrying out development in strategic places such as utilizing government land and involving outside parties to contribute to facilitating the development of culinary specialty areas. Regional government constraints include budget, unfocused central location and minimal efforts to accelerate government land use. Suggestions, the regional government is expected to carry out new innovations in culinary productivity in Serang City.